Les mots et les causes. Du Dictionnaire de Coëtanlem - Ronan Calvez (La Bretagne Linguistique, 2013)
Purchased by the city of Brest after tireless mediation on the part of Chantal Simon-Guillou, the handwritten Coëtanlem Dictionnaire is the work of Pierre Joseph Jean Chevalier de Coëtanlem de Rostiviec, who was born in Saint-Martin-des-Champs in 1749 and died in Henvic in 1827. The title that the author gave to his manuscript perfectly captures his aim: Dictionnaire de la langue bretonne […], par Dom Louis Le Pelletier […]; et c’est d’après cette édition que le présent manuscrit a été dressé avec des additions et remarques par Monsieur de Coëtanlem, en son château de Trogriffon, près Morlaix (Breton dictionary […], by Dom Louis Le Pelletier […]; the present manuscript has been compiled in line with this edition complete with additions and comments by Monsieur de Coëtanlem, Château de Trogriffon, near Morlaix). This manuscript, which is bound in eight volumes, comprises more than 8,000 pages and is the last encyclopaedic survey – in the Enlightenment sense – of Breton. Although its contents have aged considerably in some respects, this survey nevertheless remains a document of paramount importance, whose most valuable contribution lies in its linking of words with their origins.